The Effects of Microplastic Chemical Waste on the Environment : Literature Review - Indah, Dahlia Rosma; Rayani, Dewi; Nurwahidah, Nurwahidah (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Microplastics are plastic flakes or crumbs with a size smaller than 5 millimeters that come from large plastic fragments such as crackle bags, clear plastic, clothing waste, plastic bottles, styrofoam and sachets that are fragmented due to water currents and sun exposure. The danger of microplastics when they enter water, can absorb heavy metals and pollutants in the water, such as Chlorine, Phosphate, Manganese, and Chromium. As a result, the water ecosystem will be disrupted. If microplastics are ingested by fish, the fish's reproductive and growth systems are damaged. Moreover, it can interfere with human hormones if you consume the fish. The test was carried out using the Microplastic Rapid Test method using a stereo microscope connected to a monitor, so that with a magnification of 100 to 400 times, it can physically detect microplastics in the water. This researcher is a literature review. The database used in the search for this article uses Google Scholar and ScienceDirect with the keywords "microplastic, plastic waste effect, coastal microplastic, microplastic marine fish, microplastic and health effect", which has been carried out by previous researchers both from within and outside the country. The articles obtained were selected according to the topic of microplastic pollution in coastal areas, which can be downloaded, and articles published from 2018-2024. The articles reviewed were 10 articles that were relevant and according to the topic.